IMPLEMENTATION OF DISCOVERY LEARNING MODEL TO IMPROVE MATHEMATICS LEARNING OUTCOMES STUDENTS IN CLASS VII A MTs NEGERI 2 BENGKALIS - Osman; Rodiah (Jurnal Prinsip Pendidikan Matematika, 2020)
This research aims to increase the learning outcomes of students and the activity of students and teacher by applying Discovery Learning Model. The classroom action research conducted using two cycles. Each cycle consists of 2 meetings. This study also equipped with teacher activities and student activities, which are assessed using observation sheets while teaching and learning activities take place in class. Activities of students and teacher assessed by the observer. The results obtained, in test I, in the first cycle, 72% of students have achieved completeness, and fall into enough category. While in test 2, in the second cycle, 92% of students have achieved completeness, and fall into the very good predicate. The average learning activieties of students from the first cycle is 74% with enough category and the second cycle with an average of 96% is in the very good category. The average activities of teacher from the first cycle was 77,6% with a good category and the second cycle with an average of 97,5% is in the very good category. Based on the results of the research, it could be concluded that the implementation of the Discovery Learning Model can improve the activity and learning result of students of class VII A MTs Negeri 2 Bengkalis.